Analysis of physiological, technical, and tactical analysis during a friendly football match of elite U19 - Ortega, J. I.; Evangelio, C.; Clemente, F. M.; Lourenco Martins, F. M.; Gonzalez-Villora, S. (Sports, 2016)
The main objective was to analyze a friendly match of youth elite soccer players identifying the variance of tactical and physiological response parameters during the game. In addition, detecting the impact of both halves on player performance. For the purposes of this study twenty-two U19 players were analyzed playing 11v11. Activity profile, heart rate (HR and HRmax), grouped in five different zones were analyzed via Bluetooth technology, technical performance was analyzed by the Team Sport Assessment Procedure (TSAP), and tactical performance was measured by Social Network Analysis. A comparison of heart rate responses showed significant main effects in the halves (p = 0.001; h2 p = 0.623). A comparison between tactical position and technical performance had significant main effects (p = 0.001; h2 p = 0.390). Tactical position showed statistically significant effects on tactical prominence (p = 0.002; h2 p = 0.296). Therefore, fatigue is a component distinguished in technical/tactical parameters, such as volume of play and efficiency index. Results suggest that fatigue effects may constrain technical performance and, for that reason, the use of instruments to monitor the fatigue effect during matches may be suggested.